Plasmalemma Chloride Transport in Chara corallina: Inhibition by 4,4′-Diisothiocyano-2,2′-Disulfonic Acid Stilbene - Keifer, David W. (1982)
Chloride transport, presumably via a Cl(−)-2H(+) co-transport system, was investigated in Chara corallina. At pH 6.5, the control influx (3.1 picomoles per centimeter(2) per second) was stimulated 4-fold by an 18-hour Cl(−) starvation. The stimulated influx was inhibited to 4.7 picomoles per centimeter(2) per second after a 60-minute pre-exposure to 0.5 millimolar 4,4′-diisothiocyano-2,2′-disulfonic acid stilbene (DIDS). This compares with a nonsignificant inhibition of the control under similar conditions. At 2 millimolar DIDS, both stimulated and control influx were inhibited to values of 1.1 and 2.2 picomoles per centimeter(2) per second, respectively; in all cases, DIDS inhibition was reversible. Over the pH range 4.8 to 8.5, the control and DIDS-inhibited influx showed only slight pH sensitivity; in contrast, the stimulated flux was strongly pH dependent (pH 6.5 optimum). Inasmuch as changes in pH alter membrane potential, N-ethylmaleimide was used to depolarize the membrane; this had no effect on Cl(−) influx. A transient depolarization of the membrane (about 20 millivolts) was observed on restoration of Cl(−) to starved cells. The membrane also depolarized transiently when starved cells were exposed to 0.5 millimolar DIDS, but the depolarization associated with Cl(−) restoration was inhibited by a 40-minute pretreatment with DIDS. Exposure of control cells to DIDS caused only a small hyperpolarization (about 7 millivolts). DIDS may have blocked Cl(−) influx by inhibiting the putative plasmalemma H(+)-translocating ATPase. Histochemical studies on intact cells revealed no observable effect of DIDS on plasmalemma ATPase activity. However, DIDS application after fixation resulted in complete inhibition of ATPase activity. The differential sensitivity of the stimulated and control flux to inhibition by DIDS may reflect an alteration of transport upon stimulation, but could also result from differences in pretreatment. The stimulated cells were pretreated with DIDS in the absence of Cl(−), in contrast to the presence of Cl(−) during pretreatment of controls. The differential effect could result from competition between Cl(−) and DIDS for a common binding site. Our histochemical ATPase results indicate that Cl(−) transport and membrane ATPase are separate systems, and the latter is only inhibited by DIDS from the inside of the cell.